Prevalence of Limited Health Literacy in the Philippines: First National Survey - Ma. Carmen C. Tolabing; Kim Carmela D. Co; Ophelia M. Mendoza; Nona Rachel C. Mira; Romeo R. Quizon; Ma. Sandra B. Tempongko; Martin Aaron M. Mamangon; Isabel Teresa O. Salido; Peter W.S. Chang (SLACK Incorporated, 2022)
Background: Health literacy (HL) is the ability to access, understand, appraise, and apply health information across the three domains of the health continuum: health care, disease prevention, and health promotion. It is needed for people to effectively manage their health. Information on population HL level is useful for crafting appropriate and targeted interventions to improve HL. Objective: The aim of this study was to describe the HL level of Filipino people at the national and subnational levels. Methods: A cross-sectional survey was conducted between 2018 and 2019 with 2,303 randomly selected Filipino people age 15 to 70 years, using an adapted Asia version of the European Health Literacy Survey Questionnaire-47. Prevalence estimates for limited HL and the corresponding 95% confidence interval (CI) were computed at the national and subnational levels. Key Results: The nationwide prevalence of limited HL was 51.5% (95% CI, [49.5%, 53.6%]), while sub-national prevalence estimates ranged from 48.2% to 65.4%. The prevalence varied across HL dimensions, with difficulty in access to information having the highest level. Similarly, prevalence across domains was variable; health care-related HL had the highest prevalence of limited HL. The HL levels for different dimensions and domains also varied across subnational groups. Conclusion: Many Filipino people had limited HL, and prevalence estimates varied across HL dimensions, HL domains, subnational groupings, and sociodemographic characteristics. The results highlight the need for targeted interventions focusing on subgroups with limited HL and on dimensions and domains where Filipino people have limited HL. [HLRP: Health Literacy Research and Practice. 2022;6(2):e104-e112.] Plain Language Summary: The National Health Literacy Survey is the first nationwide survey on the prevalence of HL in the Philippines, involving 2,303 randomly selected Filipino residents age 15 to 70 years. Many Filipino people have limited HL, and the prevalence of HL varies across the components of HL, subnational groupings, and sociodemographic characteristics, highlighting the need for targeted interventions.